2016
DOI: 10.1095/biolreprod.116.140764
|View full text |Cite
|
Sign up to set email alerts
|

KLF10 Mediated Epigenetic Dysregulation of Epithelial CD40/CD154 Promotes Endometriosis

Abstract: Endometriosis is a highly prevalent, chronic, heterogeneous, fibro-inflammatory disease that remains recalcitrant to conventional therapy. We previously showed that loss of KLF11, a transcription factor implicated in uterine disease, results in progression of endometriosis. Despite extensive homology, co-expression, and human disease association, loss of the paralog Klf10 causes a unique inflammatory, cystic endometriosis phenotype in contrast to fibrotic progression seen with loss of Klf11. We identify here f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Moreover, consistent with the view that fibrogenesis entails epigenetic aberrations, 410 growing evidence indicates that in endometriosis fibrogenesis also involves epigenetic changes. 61,71,411,412 This raises the question as whether hormonal therapeutics can actually modify the epigenetic aberration, resulting in a gradual reverse of fibrogenesis, especially in highly fibrotic lesions such as DE. A recent study reports that, dienogest, a synthetic progestin, is effective in alleviating symptoms but does not reduce nodular size in DE, 413 suggesting that hormonal therapeutics cannot modify the epigenetic aberration that is already in place.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Moreover, consistent with the view that fibrogenesis entails epigenetic aberrations, 410 growing evidence indicates that in endometriosis fibrogenesis also involves epigenetic changes. 61,71,411,412 This raises the question as whether hormonal therapeutics can actually modify the epigenetic aberration, resulting in a gradual reverse of fibrogenesis, especially in highly fibrotic lesions such as DE. A recent study reports that, dienogest, a synthetic progestin, is effective in alleviating symptoms but does not reduce nodular size in DE, 413 suggesting that hormonal therapeutics cannot modify the epigenetic aberration that is already in place.…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…28 Upon activation (phosphorylation), p38 MAPK induces phosphorylation of its substrates at serine and/or threonine residues 29 to activate downstream molecules such as translation/transcription factors, cell cycle molecules, kinases, or scaffold proteins, resulting in a variety of cellular outputs, including cytokine production, proliferation, cycle arrest, migration, differentiation, and apoptosis. [30][31][32][33] Previously, we showed that E 2 induces p38 MAPK phosphorylation (activation) in endometrial stromal cells (ESCs) within minutes, 34 suggesting that local E 2 production in endometriosis may cause constant p38 MAPK activation. Moreover, enhanced secretion of pro-inflammatory cytokines by immune cells in an ectopic site may further increase p38 MAPK activation in endometriosis implants in a paracrine manner.…”
Section: Introductionmentioning
confidence: 97%
“…28 Upon activation (phosphorylation), p38 MAPK induces phosphorylation of its substrates at serine and/or threonine residues 29 to activate downstream molecules such as translation/transcription factors, cell cycle molecules, kinases, or scaffold proteins, resulting in a variety of cellular outputs, including cytokine production, proliferation, cycle arrest, migration, differentiation, and apoptosis. 30 33…”
Section: Introductionmentioning
confidence: 99%
“…10 Loss of KLF-mediated expression results in epigenetic dysregulation of target gene transcription and expression, resulting in the progression of endometriosis. 5,14,26 To determine whether loss of KLF11 in primary endometriotic epithelial cells altered DRD2 expression, we transfected 12Z cells with KLF11siRNA and compared DRD2 mRNA expression against scrambled control-transfected cells at 24, 48, and 72 hours (Figure 3A). As in Ishikawa cells, diminished KLF11 expression repressed DRD2 mRNA expression at least 2-fold compared to controls.…”
Section: Resultsmentioning
confidence: 99%